2005
DOI: 10.1182/blood-2005-04-1733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic implications of NPM1 mutations in acute myeloid leukemia

Abstract: Recently, somatic mutations of the nucleophosmin gene (NPM1), which alter the subcellular localization of the product, have been reported in acute myeloid leukemia (AML). We analyzed the clinical significance of NPM1 mutations in comparison with cytogenetics, FLT3, NRAS, and TP53 mutations, and a partial tandem duplication of the MLL gene (MLL-TD) in 257 patients with AML. We found NPM1 mutations, including 4 novel sequence variants, in 64 of 257 (24.9%) patients.NPM1 mutations were associated with normal kary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

32
184
10
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(231 citation statements)
references
References 47 publications
32
184
10
5
Order By: Relevance
“…Several studies emphasize the high frequency of NPM1 mutations in middle-aged adults or more elderly individuals (average age, 58 years)33 and the rare incidence of mutations in individuals younger than 35 years 1033. In our data, the age pattern for NPM1 mutations in the Iranian context seems similar to that revealed by previous investigations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several studies emphasize the high frequency of NPM1 mutations in middle-aged adults or more elderly individuals (average age, 58 years)33 and the rare incidence of mutations in individuals younger than 35 years 1033. In our data, the age pattern for NPM1 mutations in the Iranian context seems similar to that revealed by previous investigations.…”
Section: Discussionsupporting
confidence: 88%
“…In the study by Zhang et al,32 14.3% of AML patients with normal karyotype were reported to have a mutant NPM1. The other results were different: 24.9% in all AML cases,33 74.3% in normal-karyotype AMLs34 or 52.9% in normal-karyotype AMLs 10. In fact, in spite of relative differences in frequencies of these mutations, all studies imply a higher frequency of NPM1 mutations in AML cases with normal karyotype.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Several studies have observed FLT3 mutation status changes in small subsets of acute myeloid leukemia patients and have implied the prognostic importance. 10,16,[21][22][23][24][25][26][27][28][29] In aggregate, these data suggest that gain of FLT3 mutations may be associated with worse prognosis. 24,27,29,33 These patients also seem not to benefit from intensifying chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…10,16,[21][22][23][24][25][26][27][28][29] However, owing to a lack of a sufficient number of patients, no study has been able to provide statistical significant correlations between FLT3 status changes and disease progression. The goal of this study is to examine the clinical features and outcome of a large cohort of acute myeloid leukemia patients in whom FLT3 mutation status changed.…”
mentioning
confidence: 99%